Clinical efficacy of EMDR in unipolar depression: Changes in theta cordance. (February 2021) - Baptist, Joyce; Thompson, David E.; Spencer, Chelsea; Mowla, Md. Rakibul; Love, Heather A.; Su, Yile
Highlights: EMDR may be efficacious in treating unipolar depression. The dorsolateral prefrontal cortex Theta Cordance may be linked to depression. The anterior cingulate cortex Theta Cordance may be linked to depression. A reduction in Theta Cordance could indicate a return to normal function. Abstract: Eye Movement Desensitization and Reprocessing (EMDR) has demonstrated efficacy in treating major depressive disorder. EMDR increases cerebral perfusion in the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (dlPFC). Activity in the ACC and dlPFC can be measured by theta cordance (TC) but has not been examined in EMDR. Ten participants (3 men, 7 women, M age = 42.31 ± 15.03) received ten 75 ± 15 minute EMDR sessions over 6.5 ± .5 weeks. Results indicated that PHQ-9 depression scores reduced from T1 ( M  = 13.9 ± 3.31) to T11 ( M  = 6.30 ± 3.23) with EMDR (SMD = 2.30), and that fTC but not pfTC was significantly related to this change. Depression declined as fTC declined. EMDR may engage the dlPFC or ACC that modulates depression and aid in reducing fTC and thus depression levels.